2015
DOI: 10.3390/jcdd2030200
|View full text |Cite
|
Sign up to set email alerts
|

Increased Infiltration of Extra-Cardiac Cells in Myxomatous Valve Disease

Abstract: Mutations in the actin-binding gene Filamin-A have been linked to non-syndromic myxomatous valvular dystrophy and associated mitral valve prolapse. Previous studies by our group traced the adult valve defects back to developmental errors in valve interstitial cell-mediated extracellular matrix remodeling during fetal valve gestation. Mice deficient in Filamin-A exhibit enlarged mitral leaflets at E17.5, and subsequent progression to a myxomatous phenotype is observed by two months. For this study, we sought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…Previous studies have shown that inhibition of MEK/2 is a potential therapeutic option for valve disease patients (Sauls et al. ). Taken together, this suggests elastases may be potential markers for early AVD pathogenesis, consistent with our hypothesis that elastic fiber abnormalities play a fundamental role in AVD initiation and progression prior to inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that inhibition of MEK/2 is a potential therapeutic option for valve disease patients (Sauls et al. ). Taken together, this suggests elastases may be potential markers for early AVD pathogenesis, consistent with our hypothesis that elastic fiber abnormalities play a fundamental role in AVD initiation and progression prior to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, refametinib or doxycycline treatment significantly decreased the expression of proteolytic enzymes Mmp-9, and cathepsin K and L. Elastic fiber degradation products have shown promise as biomarkers of emerging disease states (Marshall et al 2013). Previous studies have shown that inhibition of MEK/2 is a potential therapeutic option for valve disease patients (Sauls et al 2015). Taken together, this suggests elastases may be potential markers for early AVD pathogenesis, consistent with our hypothesis that elastic fiber abnormalities play a fundamental role in AVD initiation and progression prior to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) was performed as we have previously reported (Norris et al, ; Sauls et al, ; Durst et al, ; Sauls et al, ). Briefly, Mouse fetuses at embryonic day (E) E17.5 were fixed in 4% paraformaldehyde, embedded in paraffin, and sectioned at 5 μm.…”
Section: Methodsmentioning
confidence: 99%
“…As Filamin-A is X-linked in both mouse and humans, we primarily focused our analyses on male mice, although some female mice have been characterized for phenotypic differences. These mice were reported previously by us and others (Feng et al, 2006;Sauls et al, 2012;Gould et al, 2015;Sauls et al, 2015). All mouse experiments were performed under protocols approved by the Institutional Animal Care and Use Committee, Medical University of South Carolina.…”
Section: Materials and Methods Gene-targeted Micementioning
confidence: 99%
See 1 more Smart Citation